A new species of Agarwalencyrtus Hayat (Hymenoptera, Encyrtidae) from China - Li, Weiqiong; Chen, Zhipeng; Zu, Guohao (Zootaxa, 2026)
A new species of Agarwalencyrtus Hayat, 1981 (Hymenoptera: Encyrtidae), Agarwalencyrtus nigroscutellatus sp. nov., is described from Chuxiong, Yunnan Province, China, and a key to all known species based on females is presented.